The impact of the organizational commitmentIn the job performance of employees of the Iraqi Insurance company (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research aims at shedding light on the impact of the organizational commitment on the performance of the Iraqi insurance company as a service company that provides many services to customers both internal (individuals working) or external, Whenever the company was able to adopt new concepts to increase the understanding and knowledge of how their attention to individuals working and to provide an appropriate working environment, and to clarify the objectives and strategies for them, and create a sense of their importance, as reflected on job performance in attracting new customers, and build long-term relationships with them . In order to achieve this, the research relied on the questionnaire as a main tool for collecting data and information by surveying the opinions of the 48 employees. Their answers were analyzed by using computational circles, standard deviations and the method of analysis.            The practical results show the significant and positive effect of the organizational commitment in performance. This is evident from the percentage of its contribution in explaining the total discrepancy which reached (81.463%) and is a good indicator of the impact of the organizational commitment in the performance of the research sample.